PENGARUH PROFITABILITAS, SALES GROWTH, DAN FIRM SIZE TERHADAP TAX AVOIDANCE (Studi Perusahaan Sektor Properties dan Real Estate yang Terdaftar di BEI Tahun 2019-2022) - Alhaque Ferdiansyah; M. Muhayin A. Sidik; Artie Arditha Rachman (Cahaya Ilmu Bangsa, 2024)
This study aims to determine the effect of profitability, sales growth and firm size on tax avoidance in property and real sector companies estate listed on BEI in 2019-2022. Variable independent in this research are profitability, sales growth and firm size. Meanwhile, the dependent variable in this research is tax avoidance. This research was tested using the SPSS version 26 test tool with tools multiple linear regression analysis. The sampling method uses purposive sampling method and obtained a total sample of 18 companies mining sector for 4 years, namely 2019-2022. So that data 72 financial report data were obtained and then data outliers were carried out So 52 data were obtained which were used as research samples. The results of this research are simultaneously profitability, sales growth and firm size influences tax avoidance. Partially profitability and sales growth has an effect on tax avoidance, but firm size does not influence on tax avoidance. Keyword: tax avoidance, profitability, sales growth, and firm size